Developing the life skills-based student worksheet for minor chemical industries - Devita Cahyani Nugraheny (Jurnal Inovasi Pendidikan IPA, 2017)
This study aimed at identifying and developing the quality of life skills-based student’s worksheet for minor chemical industries. This study was a research and development that referred to the developmental model proposed by Borg Gall. The procedures in this study consisted of four stages namely introduction, planning, product design, and product validation. The product validation was conducted by the peer reviewers, the media and material experts and the Chemistry teachers in order to gather assessment and suggestions on the quality of student’s worksheet that had been implemented to the Chemistry teachers in SMK N 1 Panjatan. The data gathering instrument that the researchers used was the product validation sheet. The results of this study showed that the product that had been generated was in the form of life skills-based student’s worksheet for minor chemical industries. On the other hand, the results of an assessment by the Chemistry teachers showed that in average the student’s worksheet fell into the “Very Good” category; as a result, the life skills-based student’s worksheet for minor chemical industries is feasible for implementation in the learning process.